STUDENTS’ PERCEPTION IN WRITING PROCEDURE TEXT - Tatin Widayanti; Nabilla Rustyana; Acep Haryudin (IKIP Siliwangi, 2019)
Abstract This study aims at investigating the students’ perception in writing procedure text and the definition of writing is different from learning other skills because writing is thinking process and need much time. Writing can help us to deepen understanding. It can help to make the sense of the information. The objective of this research is to find out students’ writing skill in procedure text. This research was a descriptive qualitative method research with a survey approach through questionnaire. The samples of this research were 20 students from 1 classes of X at SMK Jabir Al Hayyan. The data in this research were obtained through 10 questions of the questionnaire. The objective of this research is to find out students’ perception in writing procedure text. Based on the result of the data analysis who the researcher got the researcher can conclude that students’ writing skill in procedure text was positive. Most of the students knew that they have skill in writing procedure text. From the questionnaire, it was shown that the teacher may also give a good system to learn about how make a procedure text in writing skill. Keyword : Students’ Writing skill, Procedure text